A Schumpeterian Model of Protection and Relative Wages - Elias Dinopoulos; Paul Segerstrom (The Research Institute of Industrial Economics (IUI), 1996)
This paper presents a dynamic general equilibrium model of trade between two advanced countries in which both innovation and skilled acquisition rates are endogenously determined. The model offers a North-North (as opposed to a North-South) trade explanation for increasing relative wage inequality. A global reduction in trade barriers increases R&D investment and accelerates the pace of technological progress. It also reduces the relative wage of unskilled workers and results in skill upgrading, if and only if R&D is the skill-intensive activity relative to manufacturing of final products. Trade liberalization does not affect domestic relative prices in either of the two countries.
Keywords: D41; F10; F12; F13; 330; Economic growth; R&D; Protection; Relative Wages; Außenwirtschaftstheorie; Lohn; Humankapital; Innovation; Technischer Fortschritt; Handelsliberalisierung; Theorie